RUNX1: an emerging therapeutic target for cardiovascular disease. Issue 8 (10th March 2020) - Riddell, Alexandra; McBride, Martin; Braun, Thomas; Nicklin, Stuart A; Cameron, Ewan; Loughrey, Christopher M; Martin, Tamara P
Abstract: Runt-related transcription factor-1 (RUNX1), also known as acute myeloid leukaemia 1 protein (AML1), is a member of the core-binding factor family of transcription factors which modulate cell proliferation, differentiation, and survival in multiple systems. It is a master-regulator transcription factor, which has been implicated in diverse signalling pathways and cellular mechanisms during normal development and disease. RUNX1 is best characterized for its indispensable role for definitive haematopoiesis and its involvement in haematological malignancies. However, more recently RUNX1 has been identified as a key regulator of adverse cardiac remodelling following myocardial infarction. This review discusses the role RUNX1 plays in the heart and highlights its therapeutic potential as a target to limit the progression of adverse cardiac remodelling and heart failure.